Lateral thinking game / Fara Liyana Masnoor - Masnoor, Fara Liyana (2019)
In most real life situation for the teenager, they always have problem when it comes to learning of English vocabulary. Therefore, to solve their problem their need to be creative thinking to solve the problem. By that, lateral thinking is mostly suitable for problem solving to the teenager. Nowadays there are many ways to make teaching and learning process more interesting. One of the ways is through playing games. The methodology that was used to develop the lateral thinking game in web application is waterfall model and the detail on how this project will be developed such as research design, research framework, hardware and software requirement and research planning. The game is tested for its satisfaction with the develop lateral thinking in the teenagers that aged between 12-19 years old. The participant were randomly selected. Based on the result show that lateral thinking game is satisfaction. The project used educational and trivia game in teaching process which helps in learning about the lateral thinking in English vocabulary. The significance of this project can help teenager who are more accustomed to vertical thinking that is thinking only one direction of way, will be potential for developing creativity and coming with brilliant new ideas.